Application of Islamic business ethics in online marketplace: A study among Bukalapak users in Yogyakarta, Indonesia - Ilham S., Walhaarik; Andriansyah, Yuli; Sobirov, Bobur (Journal of Islamic Economics Lariba, 2024)
Introduction The rapid growth of e-commerce has revolutionized trade and consumer behavior. Bukalapak, as one of Indonesia’s leading platforms, plays a crucial role in supporting digital transformation for micro, small, and medium enterprises (MSMEs). However, the implementation of Islamic business ethics in e-commerce remains underexplored. This study investigates how Bukalapak applies Islamic business ethics principles and the relationship between security, privacy, non-deception, and reliability. Objectives The research aims to evaluate Bukalapak’s adherence to Islamic business ethics and analyze the influence of ethical dimensions (security, privacy, and non-deception) on user-perceived reliability. Method This quantitative study employed a descriptive research design using Structural Equation Modeling (SEM). Data were collected through online questionnaires distributed to 665 Bukalapak users in Yogyakarta, with variables assessed against the principles of fairness, free will, responsibility, and truth. Results The findings reveal that Bukalapak incorporates Islamic business ethics in its operations. The principles of truth and responsibility are reflected in security, privacy, and non-deception, while free will is evident in non-deceptive practices. However, security, privacy, and non-deception were not significantly correlated with reliability. Implications The study emphasizes the importance of reinforcing ethical practices to enhance user trust in e-commerce platforms. It provides actionable insights for Bukalapak and similar platforms to strengthen the alignment between ethical principles and operational reliability. Originality/Novelty This research offers a pioneering framework for assessing the application of Islamic business ethics in digital commerce. It bridges the gap between theoretical principles and practical implementation, contributing to the discourse on ethical e-commerce practices in Muslim-majority contexts.